Перспективы промышленного использования автомобильных покрышек в цементном производстве - Нзиока, Антони Мутуа; Трошин, Алексей Георгиевич; Ведь, Валерий Евгеньевич (НТУ "ХПИ", 2010)
The possibility of utilizing waste tires partly as a substitute of traditional types of fuels used in cement production has been considered. It has been shown that lower heat value for waste tires exceeds that of coal, sulfur composition in waste tires is lesser than in coal. Other than that, increased composition of iron in them aids in increasing clinker’s quality. Consequently, amount of СО2 produced in cement production substantially reduces.
Keywords: клинкер; цементная промышленность; топливо; автомобильные покрышки; теплотворная способность